Progressive Organizational Culture as a Strategy to Improve Human Resource Performance in the VUCA Era - Irnin Miladdyan Airyq; Meilani Intan Pertiwi; Aswin (Universitas Negeri Semarang, 2024)
In the face of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era, organizational sustainability depends heavily on strategic human resource management aligned with adaptive and innovative organizational culture. This study aims to investigate how progressive organizational culture acts as a strategic enabler to enhance human resource performance amidst dynamic and uncertain business environments. Utilizing a systematic literature review (SLR) approach and bibliometric analysis via VOSviewer, the study analyzes 63 selected articles from 2018 to 2025. The findings reveal that progressive cultures—characterized by adaptability, learning orientation, digital readiness, and collaborative leadership—play a pivotal role in fostering innovation, engagement, and agility in human capital. Such cultures embed performance strategies that emphasize developmental feedback, psychological safety, and cross-functional collaboration, positioning HR as a strategic driver of transformation. The study contributes to the theoretical discourse by demonstrating that organizational culture is not merely a backdrop, but a proactive strategy to optimize workforce performance in turbulent conditions.